Gender Diversity and Financial Decision-Making in Islamic Microfinance Institutions - Cintiya Anggita, Marsa; Daryono (Journal International Economic Sharia, 2025)
Objective: The current research investigates the impacts of gender diversity, leadership style, financial literacy, and organizational culture on financial decision-making, while organizational support is examined as an important moderating variable.Methods: Quantitative research, with a structured questionnaire used with managerial staff. We examine the presumed relationships using structural equation modeling (SEM) to evaluate both the direct effects and the suggested moderation.Results: Based on the results, all four independent variables have a positive and significant effect on financial decision-making. In addition, organizational support emerges as a crucial context enhancer that boosts the effects of core organizational resources on each of these relationships.Novelty: By demonstrating how the Resource-Based View of the firm can be brought together with social exchange-based mechanisms to better explain decision-making effectiveness, insight into decision-making is provided via a unified model that illuminates how organizational resources interact with contextual support to yield greater outcomes.Research Implication: This research provides valuable information that contributes to dealing with governance frameworks; hence, leaders must work towards creating an environment to take the full benefit of their human and cultural capital. It provides a tested model for enhancing strategic decision-making that can be used by different types of financial and mission-driven institutions.